Determinants of Consumers' Perceived Risk in Online Shopping : A Study - Sinha, Priyanka; Singh, Saumya (Indian Journal of Marketing, 2014)
India has nearly 74 million Internet users and with this, India has bypassed Japan to become the third largest Internet user in the world. However, only 8-10 million of the Internet users shop online. One of the reasons behind this is the virtual nature of online shops that foster various apprehensions in the minds of the consumers. The risk that consumers perceive in shopping online is multidimensional. Perception of risk by consumers depends upon various factors like their demographics, personality, shopping motivation, and so forth. It is ,therefore, important for the online marketers to not only understand the sub dimension of risks that customers perceive in online shopping, but also the variation in the risk among individuals, so as to design proper risk mitigating strategies. In the present paper, an attempt has been made to understand the impact of various sub dimensions of risk (particularly financial risk, product performance risk, time risk, and delivery risk) on attitude towards online shopping and the variation in the perception of these two sub - dimensions along the two demographic factors, that is, age and income. The research findings revealed that product performance risk, delivery risk, and financial risk negatively impact attitude towards online shopping, while time/convenience risk has no impact on attitude towards online shopping. It was also observed that consumers' perception of all the mentioned sub - dimensions of risk varies with age. However, it was found that income impacts only the perception of a product and financial risk.